Visualizing the atomic-scale origin of metallic behavior in Kondo insulators - Pirie, HS; Mascot, E; Matt, CE; Liu, Y; Chen, P; Hamidian, MH; Saha, S; Wang, X; Paglione, J; Luke, G; Goldhaber-Gordon, D; Hirjibehedin, CF; et al. (American Association for the Advancement of Science, 2023)
A Kondo lattice is often electrically insulating at low temperatures. However, several recent experiments have detected signatures of bulk metallicity within this Kondo insulating phase. In this study, we visualized the real-space charge landscape within a Kondo lattice with atomic resolution using a scanning tunneling microscope. We discovered nanometer-scale puddles of metallic conduction electrons centered around uranium-site substitutions in the heavy-fermion compound uranium ruthenium silicide (URu2Si2) and around samarium-site defects in the topological Kondo insulator samarium hexaboride (SmB6). These defects disturbed the Kondo screening cloud, leaving behind a fingerprint of the metallic parent state. Our results suggest that the three-dimensional quantum oscillations measured in SmB6 arise from Kondo-lattice defects, although we cannot exclude other explanations. Our imaging technique could enable the development of atomic-scale charge sensors using heavy-fermion probes.